Perpustakaan sebagai tempat pemenuhan kebutuhan informasi mahasiswa dalam penyelesaian tugas akhir: Studi kasus di Fakultas Tarbiyah dan Keguruan UIN Sunan Ampel Surabaya - Hary Supriyatno (IJAL (Indonesian Journal of Academic Librarianship), 2020)
The focus of the problems in this study are: 1) What information needs must be met by students in completing their final assignments at the Tarbiyah and Teacher Training (FTK) Faculty of UIN Sunan Ampel Surabaya? and 2) What is the role of libraries in meeting the information needs of students who complete their final assignments at FTK UIN Sunan Ampel Surabaya? The results, it shows that Information needed by students of the FTK at UIN Sunan Ampel in completing their final project is all collections available in the library, both printed and digital. Print collections such as books, dictionaries, journals, research results are the most sought-after sources of information, and this can be obtained through the use of general collections, reservoirs and serials, specials, references, and corners. Other information needs are fulfilled from digital collections in the form of repositories that can be available through the website http://repository.uinsby.ac.id. The Sunan Ampel UIN library has a significant role in fulfilling the information needs of students who are in the process of completing their final assignments. There are at least two supporting indicators, namely the level of visitor visits which reached 141,438 students in a year or 11,786 people each month and book-borrowing transactions totaling 75,110 copies only in the period January to August 2019 or an average of 9,388 copies per month. Several reasons that make students prefer to visit the library compared to other places such as bookstores are due to the dampness and variety of collections, comfortable places, easy access to collection utilization, friendly staff, and the suitability of collections to scientific needs.